Enabling gender equality future generations of the global world - Rodriguez, Eunice; Wejnert, Barbara (Bingley, U.K. : Emerald, 2015)
To challenge gender discrimination and to secure the world's prosperity and peace, we urgently need pro-girls and pro-women policies in the contemporary, globally developing world. Such policies could mark an era of building greater gender equality across the world by sheltering domains of women's well-being that are shown to decline. These needs can be best summarized by Kofi Annan, Secretary General of the United Nations in 2005: "When women are fully involved, the benefits can be seen immediately: families are healthier, they are better fed, their income, savings and reinvestment go up. And what is true for families is true of communities and, eventually, of whole countries." The desperately needed gender equality would honor women's place in the world, would greatly honor each country's political constituencies and enrich democratic institutions. This volume of Research in Political Sociology addresses a broad range of gender equality issues from women's status and opportunities at work, education, health, political participation, community involvement and global migration; from a vast domain of countries in Europe, America, Australia, Asia and Africa.
Turning globalization and the diffusion of democracy into opportunities for women and girls / Barbara Wejnert -- Women's portrait through gender lenses / Kanchan Saxena -- Sexual harassment against women in the workplace : a critical study on the regulatory framework in Sri Lanka / Muthukuda Arachchige Dona Shiroma Jeeva Shirajanie Niriella -- Gender, power and knowledge : deciphering the dialectics of inclusion-exclusion in academia in India / Smita Verma -- Trauma and fear of long-distance mothering among Indonesian female migrant domestic workers / Elisabeth Dewi -- Job loss, unemployment benefits, and mental health of middle-aged US women / Yujia Liu ... [et al.] -- Filling the void with food : urban gardens as safe spaces and alternatives to vacant land / Ashley Tryba -- Social neglect and oppression of widows in rural India : need for social, economic and policy implications / Jyoti Niswade -- Gender and social exclusion : a study of farmers widows of Vidarbha / Dhananjay Sontakke -- Examining women's health issues among Quechua speakers in Peru / Jennifer Tram Nguyen -- Presidential election of 2015 in Poland. What about women? / Elz<U+0307>bieta Sawa-Czajka -- Economics of portraying women in media : reinforcing stereotype role of women in advertisements in India / Jasbir Singh -- Religious discrimination and women in the Asoke Buddhist group in Thailand / Marja-Leena Heikkila<U+0308>-Horn -- Islam and Iranian women : determining the level of religious beliefs in Muslim Iranian women / Mozhgan Malekan -- Humans into birds : Italian interpretation of gender in Canadian theatre / Maria Anita Stefanelli -- Building a better world for future generations through implementation of global gender equality / Barbara Wejnert, Eunice Rodriguez.
Print version record
Keywords: Political Science -- Globalization; Social Science -- Women's Studies; Society & culture: general; Political science & theory; Sex discrimination against women; Women in development